Rurality and education relations: Metro-centricity and local values in rural communities and rural schools. (January 2019) - Beach, Dennis; Johansson, Monica; Öhrn, Elisabet; Rönnlund, Maria; Per-Åke, Rosvall
Based on ethnographic fieldwork in six different types of rural area and their schools in different parts of Sweden, this article identifies how rural schools relate to the local place and discusses some of the educational implications from this. Recurrent references to the local community were present in some schools and people there explicitly positioned themselves in the local rural context and valorised rurality positively in education exchanges, content and interactions, with positive effects on young people's experiences of participation and inclusion. These factors tended to occur in sparsely populated areas. An emphasis on nature and its value as materially vital in people's lives was present as was a critique of middle-class metrocentricity. Such values and critique seemed to be absent in other areas, where rurality was instead often represented along the metrocentric lines of a residual space in modernizing societies.